Implementation of The Word Guessing Method to Improve Students' Activeness in Catholic Religious Education Lessons - Maria Yulita C. Age; Maria Novita Yuni Deda (Green Publisher Indonesia, 2024)
Student activity is an activity or activity carried out by the teacher to see the extent to which students are able to comprehend and comprehend the lessons given. In this case, teachers or instructors should prepare themselves such as teaching materials and use good learning methods so that students can comprehend and comprehend the lessons given. It is known that the fifth grade students at SDK Wolondopo 2 are less active in participating in Catholic Religious Education (PAK) lessons. Students' learning motivation is still relatively low, during the learning process there are still many students who do not pay attention to the teacher who is explaining the material, lessons tend to be teacher-centered and students are less actively involved during the learning process and student learning achievement decreases. The problem in this research is how effective the word guessing method is in PAK learning to increase the activity of class VI students at SDK Wolondopo 2. The aim is to find out the effectiveness of the word guessing method in PAK learning to increase the activity of class VI students at Wolondopo SDK 2. This research method is action research. class using a qualitative approach. Data collection techniques are observation and documentation. The data analysis technique used in the research is Classroom Action Research (PTK) in which there are influences and relationships between variables. The research results show that using the word guessing method can increase student activity.